2007
DOI: 10.1016/j.jada.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving the School Food Environment: Results from a Pilot Study in Middle Schools

Abstract: Our objective for this study was to examine the feasibility of instituting environmental changes during a 6-week pilot in school foodservice programs, with long-term goals of improving dietary quality and preventing obesity and type 2 diabetes in youth. Participants included students and staff from six middle schools in three states. Formative assessment with students and school staff was conducted in the spring of 2003 to inform the development of school foodservice policy changes. Thirteen potential policy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 19 publications
0
84
0
2
Order By: Relevance
“…Similar to other studies, 24 the largest barrier to providing a daily FV snack was cost; which included the actual purchase of FV, and also the time to prepare and the potential for waste associated with fresh FV. The budget did not allow for additional staff to be hired to prepare an after-school snack, which meant GLs were the ones responsible to ensure snack was prepared.…”
Section: Discussionmentioning
confidence: 67%
“…Similar to other studies, 24 the largest barrier to providing a daily FV snack was cost; which included the actual purchase of FV, and also the time to prepare and the potential for waste associated with fresh FV. The budget did not allow for additional staff to be hired to prepare an after-school snack, which meant GLs were the ones responsible to ensure snack was prepared.…”
Section: Discussionmentioning
confidence: 67%
“…Inclusion criteria were at least a 50% ethnic minority student population (African American, Native American, and Hispanic), the groups most at risk for type 2 diabetes (4), and at least 50% of the students eligible for free/reduced price meals. There were 13 pilot intervention goals, 6 of which were specific to the a la carte/ snack bar area, with the others pertaining to the National School Lunch Program (9). This article presents data about the success of the a la carte/snack bar goals (reduce all regular chips serving size bags to ≤1.5 oz, increase lower-fat chip offerings by 25%; offer bottled water in a 20-oz size, and limit all sweetened beverages to ≤12 oz) most likely to impact energy balance.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 13 a la carte/snack bar items were sold daily in the Texas schools, 11 to 17 in the North Carolina schools, and 22 to 31 in the California schools. More details about the schools can be found in a previous publication (9). A research dietitian at each field center worked with the school foodservice manager to implement the intervention goals, and conducted in-service trainings with all foodservice workers to explain changes and enlist support for the intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] While the literature on intervention is limited and focuses on early adolescents, studies have consistently shown that school-based interventions are desperately needed and can be effective. [27][28][29][30][31] For example, Planet Health, an interdisciplinary school intervention for early adolescents in Massachusetts, reduced television viewing hours overall in boys and girls, increased fruit and vegetable consumption and smaller increment in energy intake in girls, and decreased obesity among girls. 32 Alternatively, a randomized trial of school-based environmental and policy changes among early adolescents was successful in increasing physical activity and reduced BMI among boys.…”
Section: Discussionmentioning
confidence: 99%